El desarrollo físico e intelectual a través de la práctica de basquetbol en niños de 8 a 10 años en FEDEORO, de la ciudad de Machala, año 2012. - Aguilar Reyes, Saure Constante (2012)
The development of physical and intellectual abilities in children plays a very important role in the development of his personality, the discipline of basketball in children aged 8 to 10 years is one of the sports tools to develop their physical conditions or mentally to face environmental conditions around them.